Financial Literacy, Digital Inclusion, and Sustainable Economic Governance: Comparative Evidence from the Western Balkans - Berisha Dranqolli, Vlora; Shala, Albulena; Rayfield, Blake; Collakovic, Anesa; Mema, Kaltirna; Hamiti, Era; Sadikaj, Besa (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
This study examines the relationship between financial literacy, digital financial inclusion, and sustainable economic governance in the Western Balkans. Using a comparative research design, the analysis integrates data from the S&P Global Financial Literacy Survey, OECD/INFE surveys, PISA 2018, and complementary indicators, alongside macroeconomic variables such as unemployment, GDP trends, and remittances. The findings reveal notable cross-country variation. While financial literacy levels remain relatively similar across the region, digital financial inclusion has expanded significantly between 2011 and 2024, particularly in account ownership and debit card usage. Countries with higher levels of financial inclusion tend to exhibit more favorable economic outcomes, including lower unemployment and reduced reliance on remittances, whereas weaker financial capability and access are associated with greater structural constraints. Persistent challenges include limited participation in credit markets and ongoing gender disparities in access to financial services. The results suggest that financial literacy and digital inclusion operate jointly within a broader economic and institutional context, shaping patterns of economic resilience and development. Strengthening financial capability alongside expanding access to financial services is therefore essential for supporting inclusive and sustainable economic governance in the region.